Exploring the Impact of Social Media Use on English Vocabulary Learning among Non-English Major University Students - wilson, agus; Anam, Syafi'ul (SCOPE: Journal of English Language Teaching, 2024)
This study aimed to investigate the impact of social media use on vocabulary learning of English as a Foreign Language (EFL) among Indonesian first-semester EFL learners. The researchers used a research design grounded in the Technology Acceptance Model (TAM) and employed a questionnaire to collect data via Google Forms involving 176 participants. The participants of the study (N=176) consisted of 103 men (59%) and 73 women (41%). The findings revealed that social media can be an effective tool for vocabulary learning and identified factors within social media platforms that contribute to or hinder the effectiveness of vocabulary learning for EFL students at one private university in Jakarta. This study identified the factors of safety and privacy, ease of access and navigation, quality and relevant content, interactivity and participation, and constructive feedback. A key implication of this study is that integrating social media into language learning curricula can serve as a powerful strategy to improve vocabulary retention and student engagement in a digital age. This approach not only leverages the familiarity and accessibility of social media but also aligns with contemporary educational practices. Future studies could explore several avenues, including the long-term effects of social media engagement on vocabulary retention, the specific features of social media that contribute most to vocabulary learning, the comparative effectiveness of different social media platforms, and investigate the impact of social media on other language skills, such as reading comprehension and writing proficiency, to provide a more comprehensive understanding of its role in language education.